Global incidence of oesophageal cancer by histological subtype in 2012. Issue 3 (15th October 2014) - Arnold, Melina; Soerjomataram, Isabelle; Ferlay, Jacques; Forman, David
Abstract : Objective: The two major histological types of oesophageal cancer—adenocarcinoma (AC) and squamous cell carcinoma (SCC)—are known to differ greatly in terms of risk factors and epidemiology. To date, global incidence estimates for individual subtypes are still lacking. This study for the first time quantified the global burden of oesophageal cancer by histological subtype. Design: Where available, data from Cancer Incidence in Five Continents Vol. X (CI5X) were used to compute, age-specific, sex-specific and country-specific proportions of AC and SCC. Nine regional averages were computed for countries without CI5X data. The proportions were then applied to all oesophageal cancer cases from GLOBOCAN 2012 and age-standardised incidence rates calculated for both histological types. Results: Worldwide, an estimated 398 000 SCCs and 52 000 ACs of the oesophagus occurred in 2012, translating to incidence rates of 5.2 and 0.7 per 100 000, respectively. Although SCCs were most common in South-Eastern and Central Asia (79% of the total global SCC cases), the highest burden of AC was found in Northern and Western Europe, Northern America and Oceania (46% of the total global AC cases). Men had substantially higher incidence than women, especially in the case of AC (male to female ratio AC: 4.4; SCC: 2.7). Conclusions: These first global estimates of oesophageal cancer incidence by histology suggested a high concentration of AC in high-income countries with men being at much greater risk. This quantification of incidence will aid health policy makers to plan appropriate cancer control measures in the future.